CREATING PRINCIPLES OF CONSTRUCTING AND PRESERVING THE MONUMENTS OF “DESHAN KALA” - Salayev , E.A.; Reimbaev, Sh.S. (Educational Research in Universal Sciences, 2024)
This article provides information about the brick thatched wall which is located in the centre of Khiva City and contains five neighborhoods. The wall was built in 1842 and has been finished within 36 days. This Ichan Kala wall amazes and attracts millions of foreign and local visitors and proves that construction and architecture were well developed in the ancient Khorezm.